Hubungan Stres Akademik dengan Kesehatan Mental Remaja: The Relationship Between Academic Stress and Mental Health of Adolescents - Santoso, Edi; Adiansyah, Tegar (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Academic Stress often appears in adolescents, many factors affect including high academic demands. This academic Stress, if not immediately intervened, can have a negative impact on health, especially mental health. The purpose of this study is to find out whether there relationship between academic Stress and adolescent mental health of grade XI students of SMAN 1 Pule, Trenggalek Regency. This research is a correlationa lresearch with an approach cross- sectional. The population is XI students of SMAN 1 Pule, the sample is 119 determined by the cluster random sampling. The instrument used is in the form of a questionnaire to measure the level of academic Stres and mental health of students. Analysis using tests chi-square. The results showed that 65% of respondents experienced moderate academic Stress, and 95.8% also showed signs of poor mental health. Analysis chi-square It produces a P value < 0.05, which means that there is a relationship between academic Stress and adolescent mental health.The conclusion of this study is that there is a relationship between academic Stress and adolescent mental health at SMAN 1 Pule Trenggalek Regency. It is recommended for schools to develop psychological support programs for students, as well as conduct socialization about academic Stress management to improve students' mental health.